Sistem Informasi Pendataan Pengunjung Menggunakan Framework Laravel - Yunizal, Edri; Lusiana, Firna (Universitas Methodist Indonesia, 2024)
Indonesia is a country with enormous tourism potential. A condition that should be able to utilize data for decision making to increase traveler satisfaction. Unfortunately, tourist attractions still collect visitor data using ledgers, a solution that is still manual. Several previous studies have seen this as a problem, and then offered solutions such as website, registration and e-ticketing. However, the existing solutions are still general data collection which does not yet support detailed data such as types and categories of visits. This research proposes developing a solution by including data on agency, category, type of visit, purpose of visit, and area of origin. A solution that will make it easier to collect detailed data and quickly search for data. Geopark Informations Center Ranah Minang Silokek then became the object of a case study, where the visit categories can be divided into geotourism, geoeducation, geoculture, and other visits. The solution also delivers improved software quality, reduced initial costs, and improved user experience by leveraging the Laravel framework. Research methods include literature study, needs analysis, system design, system implementation, and report writing. A solution that is able to provide a visitor data collection information system with the capability to accommodate detailed visitor data. A solution that makes it easier to quickly search for information and will be able to provide data that will later be needed by data science-based solutions.